P–423 Lower cytotoxicity: Altered natural killer cell activation in recurrent implantation failure. (6th August 2021) - Strobel, L; Vomstein, K; Kyvelidou, C; Hofer-Tollinger, S; Ebner, S; Troppmair, J; Toth, B
Abstract: Study question: Within this prospective study, we aim to differentiate immune cell subpopulations in recurrent implantation failure (RIF) patients and fertile controls. Summary answer: A misbalanced immune profile of NK cell subpopulations is present in RIF patients and might be a potential risk factor that requires further detailed analysis. What is known already: So far, there is no conclusive opinion on the prognostic value of testing immune cell populations in women with RIF. Increased numbers of cytotoxic (CD56dimCD16bright) peripheral natural killer (pNK)-cells and CD56brightCD16dim mainly in the uterus occurring NK cells (uNK) seemed to be more prevalent in RIF patients. NK cell cytotoxicity is regulated by a complex interaction of activating and inhibiting receptors, such as the NKGD2 and natural cytotoxicity receptors including NKp46, NKp30 and NKp44. Dysregulated pNK cells could affect the adhesion and implantation of the embryo thereby contributing to RIF. Study design, size, duration: Within this prospective study between March 2018 and August 2020 immune diagnostics of pNK cells and subpopulations as well as regulatory T-cells in RIF patients (defined as ≥ 3 failed fresh or frozen embryo transfers of good quality embryos (Istanbul criteria) and non-pregnant controls (nulli- and multipara) were performed using flow cytometry analysis. Participants/materials, setting, methods: In total, n = 42 RIF and n = 85 controls were included. Absolute numbers and percentages of total lymphocytes of CD56dimCD16bright, CD56brightCD16dim NK cells, CD45+CD25+FoxP3+-regulatory T-cells and activation markers (CD57+, CD62L+, NKGD2+, NKp46+) were measured in patients and controls (n = 60 nulligravida, n = 25 para) in the mid-luteal phase. Statistical analysis was performed using SPSS Version 26 considering p < 0.05 statistically significant. Main results and the role of chance: RIF patients showed significantly lower numbers and percentages of CD56dimCD16bright pNK cells (mean±SD per µl: 187, 5±113, 3 vs. 281, 9±163, 4 p = 0.001;%: 87, 4±8, 8 vs. 90, 6±6, 0 p = 0.017) and higher levels of CD56brightCD16dim pNK cells (mean±SD per%: 10, 5±8, 3 vs. 7, 6±5, 5 p = 0.021) compared to controls. Further, lower percentages of CD56dimCD16brightCD62L + (mean±SD per%: 23, 5±11, 1 vs. 32, 0±14, 0 p = 0.001), CD56dimCD16brightNKGD2 + (mean±SD per%: 94, 0±6, 8 vs. 96, 4±4, 2 p = 0.014) and CD56dimCD16brightNKp46 + (mean±SD per%: 65, 8±19, 5 vs. 76, 1±14, 0 p = 0.001) were observed in RIF patients (p < 0.05). A different activation of pNK cells represented by high levels of CD62L+, NKGD2+, NKp46+ surface markers in controls and higher levels of CD56brightCD16dim pNK cells in RIF patients could contribute to RIF. No difference was present in levels of CD45+CD25+FoxP3+-regulatory T-cells within the study population. Limitations, reasons for caution: As controls composed out of not only nulli- but also multipara, higher levels of pNK cells in controls, could be induced by fetal microchimerism in multiparas, however, results remained significant after removing multipara from statistical analysis. Wider implications of the findings: These findings condense into the assumption of a non-linear association between NK cytotoxicity and successful pregnancy. A lower NK cytotoxicity in RIF patients could potentially lead to an altered immune environment impeding a successful implantation process. Trial registration number: Drks00020803